A mindful yoga intervention for young women with major depressive disorder: Design and baseline sample characteristics of a randomized controlled trial. Issue 2 (17th February 2020) - Vollbehr, Nina K.; Hoenders, H.J. Rogier; Bartels‐Velthuis, Agna A.; Nauta, Maaike H.; Castelein, Stynke; Schroevers, Maya J.; Stant, A. Dennis; de Jong, Peter J.; Ostafin, Brian D.
Abstract: Objectives: Despite the gains made by current first‐line interventions for major depressive disorder (MDD), modest rates of treatment response and high relapse indicate the need to augment existing interventions. Following theory and initial research indicating the promise of mindful yoga interventions (MYIs), this study examines mindful yoga as a treatment of MDD. Methods/Design: This randomized controlled trial uses a sample of young females (18–34 years) to examine the efficacy and cost‐effectiveness of a 9‐week manualized MYI added to treatment as usual (TAU) versus TAU alone. Primary outcome measures consist of clinician‐administered (Hamilton Depression Rating Scale) and self‐report (Depression‐Anxiety‐Stress Scales) measures of depression. Underlying mechanisms will be examined, including rumination, negative self‐evaluation, intolerance of uncertainty, interoceptive awareness, and dispositional mindfulness. Assessments were conducted at preintervention and will be conducted at postintervention, 6‐, and 12‐month follow up. Results: The baseline sample consists of 171 females (88 were randomized into the MYI), reporting a baseline M age = 25.08 years ( SD age = 4.64), M Hamilton‐depression = 18.39 ( SD Hamilton = 6.00), and a M DASS‐depression = 21.02 ( SD DASS = 9.36). Conclusion: This trial will provide important information regarding the benefits of adding yoga‐based interventions to TAU for young women with MDD and the mechanisms through which such benefits may occur.